Protein folding while chaperone bound is dependent on weak interactions - Kevin Wu (Nature Portfolio, 2019)
Spy is an ATP independent chaperone that allows folding of its client protein Im7 while continuously bound to Spy. Here the authors employ kinetics measurements to study the folding of another Spy client protein SH3 and find that Spy’s ability to allow a client to fold while bound is inversely related to how strongly it interacts with that client.